2019
DOI: 10.1002/csr.1868
|View full text |Cite
|
Sign up to set email alerts
|

Connecting earnings management and corporate social responsibility: A renewed perspective

Abstract: This paper aims at discovering the association between earnings management (EM) and gender diversity in boards of directors as a predictor of the corporate social performance (CSP) of non‐smallmedium‐sized enterprises in the context of corporate social responsibility (CSR). The existence of a broad literature on the topic allows us to assess EM and its relations with CSR. We used an OLS regression analysis and the accrual quality measure as an EM proxy to investigate our sample of 697 Italian non‐small and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 78 publications
(133 reference statements)
0
16
0
1
Order By: Relevance
“…Board gender diversity (BGEND) plays a vital role in improving the quality of reporting (Dani et al, 2019;Maglio et al, 2020). The literature suggests that representation of more female directors may: enhance board effectiveness in various issues (Arioglu, 2020), improve the board's monitoring and advisory roles, increase their ethical behaviours, deter opportunistic behaviour in EM practices (Fan et al, 2019;Harakeh et al, 2019), and thereby promote the quality of reporting.…”
Section: Board Gender Diversity Corporate Social Responsibility and mentioning
confidence: 99%
See 2 more Smart Citations
“…Board gender diversity (BGEND) plays a vital role in improving the quality of reporting (Dani et al, 2019;Maglio et al, 2020). The literature suggests that representation of more female directors may: enhance board effectiveness in various issues (Arioglu, 2020), improve the board's monitoring and advisory roles, increase their ethical behaviours, deter opportunistic behaviour in EM practices (Fan et al, 2019;Harakeh et al, 2019), and thereby promote the quality of reporting.…”
Section: Board Gender Diversity Corporate Social Responsibility and mentioning
confidence: 99%
“…According to agency theory, monitoring is one of the main functions performed by corporate boards (Jensen & Meckling, 1976). Female directors are more likely than men to improve the corporate board's monitoring effectiveness over the quality of reporting practices, deterring opportunistic EM practices, increasing directors' ethical behaviour, and improving earnings quality (Arioglu, 2020;Harakeh et al, 2019;Maglio et al, 2020;Orazalin, 2019;Srinidhi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existing results are inconclusive. Some found that higher CSR activities lowered opportunistic financial disclosures (Hirst, Koonce, & Venkataraman, 2008; Hutton & Stocken, 2009; Kim, Park, & Weir, 2012; Dhaliwal, Radhakrishnan, Tsang, & Yang, 2012: Maglio, Rey, Agliata, & Lombardi, 2020; Buertey, Sun, Lee, & Hwang, 2020), while others found a negative effect of CSR on management forecast quality (Martínez‐Ferrero, Banerjee, & María Gárcía‐Sanchez, 2016; Prior et al, 2008; Salewski & Zulch, 2014).…”
Section: Corporate Social Responsibility and Market‐based Firm Performentioning
confidence: 99%
“…, 2012:Maglio, Rey, Agliata, & Lombardi, 2020;Buertey, Sun, Lee, & Hwang, 2020), while others found a negative effect of CSR on management forecast quality(Martínez-Ferrero, Banerjee, & María Gárcía- Sanchez, 2016;Prior et al, 2008;Salewski & Zulch, 2014).Do CSR activities affect the quality of disclosed financial information, and, if so, how?Grewatsch and Kleindienst (2017) reviewed the empirical studies that examined the relationship between CSP and financial performance (CFP) and found that many studies lack the contingency perspective that integrates the relationship between CSP and CFP into strategic management.This study investigated the effects of CSR intensity on investment performance and identified the channels through which it effects management forecast behavior in the context of Japanese firms from 2007 to 2016. Using the CSR moderator model framework, we posited management earnings forecasts as predictors and investment performance as outcomes, with CSR intensity as a moderator.If CSR intensity is perceived as a signal of firm-level trust and self-discipline ability for transparency, it not only directly influences investment performance but may also indirectly influence the relationship between management earnings forecasts and investment performance.…”
mentioning
confidence: 99%